Hypoperfusion With Vomiting, Abdominal Pain, or Dizziness and Convulsions: An Alert to Fulminant Myocarditis in Children - Zhu, Angang; Zhang, Tian; Hang, Xiaobi; Zhang, Xiaoguang; Xiong, Yingying; Fang, Tao; Chen, Mingwu (Frontiers in Pediatrics, 2020)
Objective: To investigate the clinical features, treatment methods, and outcomes of fulminant myocarditis (FM) in children. Methods: The clinical data of 23 children with FM hospitalized in the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China (Anhui Provincial Hospital) and Anhui Provincial Children's Hospital from January 2011 to September 2019 were retrospectively analyzed. Results: Among the 23 patients analyzed, 10 were male and 13 were female. The patients aged from 6 months to 14 years (6.5 ± 3.4 years), and 18 patients were over 3 years. There were 14 cases with respiratory symptoms, 16 cases with gastrointestinal symptoms, 15 cases with neurological symptoms, and 19 cases with hypoperfusion manifestations. Creatine kinase MB (CK-MB) and cardiac troponin I (CTnI) levels were increased in 19 and 21 cases, respectively. Electrocardiography (ECG) showed ST-T changes in 18 cases and atrioventricular blocks (AVB) in 15 cases. Echocardiography (ECHO) showed cardiac chamber enlargement (CCE) in 8 cases, left ventricular systolic dysfunction in 5 cases, decrease in left ventricular ejection fraction (LVEF) in 4 cases, reduction in wall motion in 2 cases, and pericardial effusion in 7 cases. Intravenous immunoglobulins (IVIG) and glucocorticoids were administered to 19 and 20 patients, respectively. Fourteen patients were treated with temporary pacemakers, one patient received extracorporeal membrane oxygenation (ECMO), one patient received continuous renal replacement therapy (CRRT), and one patient received ECMO combined with CRRT. Twenty patients improved at discharge, and three patients died. Conclusion: Preschool and school-age children showing hypoperfusion symptoms, such as paleness, cold clammy limbs, and capillary refill time (CRT) extension, accompanied by vomiting, abdominal pain, dizziness, convulsions, and other symptoms, should be carefully examined for FM. CK-MB, CTnI, ECG, and echocardiogram need to be performed at the earliest. In the early stages of FM, vital signs should be actively monitored, high-dose IVIG and glucocorticoids should be administered, and life support technologies such as temporary pacemakers, ECMO, and CRRT should be used to increase the survival rate of children with FM as needed.